PAYAKUMBUH MAYOR GOVERNMENT LEADERSHIP IN MANAGING CLEANLINESS 2015-2017 - Putra, Zaki Maulana; ", Isril (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research was conducted with the aim to find out the Mayor's Payakumbuh Policy in managing cleanliness in 2015-2017. The success of Payakumbuh City won the Adipura award 3 times in a row, giving rise to a curiosity about the policies issued by the Mayor of Payakumbuh in managing cleanliness and also the efforts of the Mayor of Payakumbuh in implementing the policy. The theory used in this study is situational leadership theory and leadership nature theory. This study uses analytical descriptive method with qualitative research. The type of data used in this study is primary data and secondary data obtained through interviews directly with informants who are considered to know and understand the problems in the field, documentation and observation.Based on the explanation above, it can be concluded that the Mayor of Payakumbuh can be said to successfully lead the City of Payakumbuh in the management of cleanliness, due to the achievements obtained in the form of the Adipura Cup three years in a row. Therefore, it needs to be felt to find out what Mayor Payakumbuh is doing in managing cleanliness, so that it can be said to be successful at this time.The success of the Mayor of Payakumbuh in the field of hygiene management because the policies issued are relevant to the current state of Payakumbuh City. Furthermore, the efforts made by Mayor Payakumbuh to be able to embrace all parties, subordinates, the public and also the private sector, to jointly participate in managing the cleanliness of Payakumbuh City.Keyword: Leadership, Policy, Manage Cleanliness.